An analysis of self-compassion influence on posttraumatic growth with resilience as moderation variable - Adetya, Sandra (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
Affair becomes one of traumatic events for an individual which can cause stress. The purpose of this research was to find out the influence of self-compassion on posttraumatic growth on affair victim (the wife) with resilience as the moderation variable. This research employed quantitative method and the collected data were then processed statistically by using Moderated Regression Analysis (MRA). This study involved 100 victims of infidelity. The instruments used are self-compassion scale, posttraumatic growth scale; resilience. The research result proved that self-compasstion was sufficient to help increasing posttraumatic growth on the wife who becomes a victim of an affair.